Smart systems design, applications, and challenges - Rodrigues, João M. F.; Cardoso, Pedro J. S.; Monteiro, Janio; Ramos, Célia M. Q. (Advances in computational intelligence and robotics (ACIR) book series., 2020)
"This book explores new trends and applications in smart systems"--